Police Digital Forensics Functional in Handling Hate Speech Crimes in Cyberspace - Junaidi, Junaidi; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
The Police Criminalistics Laboratory is part of the organizational structure of the Police which has the task or function as a supervisor, implementer of criminalistics or Forensics, as a science whose application is to provide technical support in the investigation/investigation of criminal acts. This study aims to Functional Digital Forensics of the Police in Handling Hate Speech Crimes in Cyberspace. In this study, the approach method used is: a normative legal approach (normative legal research method). library legal research conducted by examining library materials or secondary data alone. The research specification used is Descriptive Analytical, namely an effort to analyze and explain legal problems related to objects with a comprehensive and systematic description of everything related to the Functional Digital Forensics of the Police in Handling Hate Speech Crimes in Cyberspace. In the context of Indonesian law, digital forensics has been legitimized as valid evidence through the recognition of electronic evidence in the Electronic Information and Transactions Law (UU ITE), as well as the Draft Criminal Procedure Code which accommodates electronic evidence as part of legal evidence. Therefore, the use of digital forensics must be carried out by competent experts and follow established procedures so that the results can be legally accepted in court. Digital forensics plays a vital role in proving the perpetrators in hate speech crimes in cyberspace. Through a scientific process that can be accounted for, digital forensics is able to reveal who exactly "everyone" is referred to in the criminal article. Its main function is not only in collecting evidence, but also in validating, authenticating, and presenting digital data as valid legal evidence. In this digital era, the success of law enforcement against hate speech is highly dependent on the sophistication and integrity of digital forensics.